Fracture of the Body's Hamate Bone: Open Reduction Internal Fixation by Double Approach—A Case Report - Salvador Marín, Jorge; Brotons Baile, Antonia; Cardona Vives, Nuria; Vargas Prieto, Jaime Francisco; Pérez Alba, José Manuel; Martínez López, José Fernando (Revista Iberoamericana de Cirugía de la Mano, 2018)
Hamate fractures are rare. Their treatment depends on the displacement and type of fracture. We present the case and surgical technique of a 33-year-old male patient, who is a manual worker, with a displaced fracture of the body of the hamate bone associated with dislocation of the fourth and fifth metacarpal (MC) bones. The patient was operated on with a double palmar and dorsal approach directly over the hamate and the body hook, respectively, which was performed to improve the control reduction and avoid damaging the neighboring vascular and nerve structures. The open reduction internal fixation (ORIF) was performed by inserting mini-screws in a dorsal to palmar direction. Later, the dislocations were reduced and fixed with Kirschner wires between the fourth and fifth MC bases, and between the fourth MC base and the capitate bone. The patient was discharged 2.5 months after the fracture. The Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire outcome measure was 5 points at 6 months postsurgery.
Keywords: carpal fracture; carpometacarpal dislocation; double dorsal and palmar approach; hamate fracture; open reduction internal fixation